VALIDATION OF TROPICAL RAINFALL MEASURING MISSION (TRMM) RAINFALL DATA FOR THE KAPUAS HULU DISTRICT AREA - Tangkadas, Charles Gonzaga; Soeryamassoeka, SB; Nirmala, Azwa (Fakultas Teknik Universitas Tanjungpura, 2023)
Rainfall is a critical element in the hydrological cycle. Therefore, accurate rainfall inputs are essential for reliable hydrological predictions in various water resource analyses. Many areas in the tropics depend on rainfall for multiple needs because rainfall has an essential influence on numerous aspects of human life, especially in water resources planning and management. However, not all areas have rainfall recording stations using manual rain and gauges or automatic rainfall recorders, so rainfall records are rarely complete; this is also the case in Kapuas Hulu District, West Kalimantan Province.This research article presents the results of TRMM satellite rainfall data research in Kapuas Hulu District, with validated rainfall data, 1-day maximum rainfall data, and rainfall amount data. Validation stages are carried out by calibrating, verifying, and correcting rainfall data. As a comparison station (dependent variable) is the BMKG Pangsuma observation station, KPH-06 Nanga Kantuk, KPH-08 Ng. Silat, KPH-09 Jongkong, KPH-13 Tepuai in 1998-2019.The results of the analysis show that the best correlation value on the amount of rainfall data and 1-day maximum rainfall data obtained from Grid 30 TRMM of 0.83 and 0.82 with the observation station is BMKG Pangsuma Station, and then the equation obtained from the analysis results on the grid is used as an equation for correction. The data correction equation for the amount of rainfall is Y = 1.1578 X - 98.5547, and the 1-day maximum rainfall data correction equation is Y = 1.2036 X - 28.4197.